It's my hand that wrote! - Magade, Mncedi (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2020)
This collection of short stories experiments with the idea of the text as it constitutes the world just as much as it is constituted by the world. These short stories use the text as a way to respond to struggles faced by people whose identities do not conform to society's standards. The stories in here navigate between fantastic and experiential writing which allows the text to speak in its own language. The writing is influenced by that of Mthuthuzeli Matshoba for the realist approach in telling the stories. Ayi Kwei Armah's writing in Fragments for experientialism that focuses on the dead and the living and which makes specific references to the idea of home "“ particularly for those who always find it hard to belong. And that of Bruce Sterling's creation of explosive imagery in science fiction that sticks in the reader's mind as portrayed in his short story we see things differently. Angela Carter's brilliance in writing short stories and her approach to magical realism has also been a powerful influence. In telling these stories using a hybrid/fluid approach, I hope to come to terms with being a different "being" . It is to find ways of telling myself that it is okay to be queer, that to be a misfit is no sin. To say this in a language that gives meaning to my own struggles of being. This work is a combination of three disjointed moments of the narrator's life experiences which are exposed in three sections; It's My Hand That Wrote, (Un)Tying The Knot and Thoughts. The aim of creating these three moments is to let the reader dive a variety of "truths" of the narrator's life, instead of aiming to achieve a coherent single "Truth" about one's life. It's My Hand That Wrote explores both the unusual and inconsistency of life in a chaotic but explorative fashion.
Keywords: South African fiction (English) -- 21st century